IMPLEMENTASI KEBIJAKAN PENGEMBANGAN USAHA EKONOMI PRODUKTIF DALAM PENGENTASAN KEMISKINAN DI DESA - pairan, pairan (Babes Litbang Yankessos, 2019)
The main problem of poverty is not the obsensce capital on lack of human of human resource, but it is not regarded a problem by the local society or the poors themselves. To convince the society using mindset is the prior to social policy. So, common efforts to empower society is getting an important role, in order to pick the poor up from their poverty, needed a policy in the benefit of them. A great hope, that economic development of the poor society will be succesfully conducted by the goverment. This is based on real fact that the goverment has some certain institutions to assist policy process, planning, adminnistrating in social development process. The research method used qualitaty and case study approach. Data was collected by observation, interviewing, focus group discussion, and documentation. Data analysis used qualitaty description by using interactive model, data reduction, data presentation and conclution. Data validity test was used triagulation method. The research showed that formulation policy of poverty alleviation in village can use policy model of local imtiative development in poverty alleviation of community based through sustainable livelihood through three steps activities of social economic mapping, economic empowerment by UEP, and mechanism marketing of UEP products, social mids delivery through E-warung. UEP is sinergized with the local natural resources like bamboo to provide added value of the bamboo plants.